1988
DOI: 10.1111/j.1365-3024.1988.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Eitneria tenella: immunological diversity between asexual generations

Abstract: In the development of a normal strain, WIS, of Eimeria tenella there are three generations of schizogony whereas in an attenuated line, WIS-F-96, derived from WIS, the second and third are absent. Chickens immunized by infection with WIS-F-96, however, were highly resistant to oral challenge with sporulated oocysts of WIS, and histological studies indicated that the immune response was directed against the sporozoites from that challenge inoculum. When challenge of the WIS-F-96-primed chickens consisted of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Of particular interest is the low level of cross-reactivity between antigens of the sporozoite and the first generation merozoite and between the first and second generation merozoite. This is in agreement with the results of a previous study that showed both poor immunological cross-protection between these stages and also, from blots probed with convalescent chicken sera, that the first and second generations of merozoites were antigenically different (McDonald et al 1988). In a study on fractionation of organelles of Eimeria tenella, we found that the only reduced polypeptide of sporozoites which was strongly recognized by antisera to first generation merozoites was a microneme-associated antigen of around 100 kDa (Kawazoe et al 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of particular interest is the low level of cross-reactivity between antigens of the sporozoite and the first generation merozoite and between the first and second generation merozoite. This is in agreement with the results of a previous study that showed both poor immunological cross-protection between these stages and also, from blots probed with convalescent chicken sera, that the first and second generations of merozoites were antigenically different (McDonald et al 1988). In a study on fractionation of organelles of Eimeria tenella, we found that the only reduced polypeptide of sporozoites which was strongly recognized by antisera to first generation merozoites was a microneme-associated antigen of around 100 kDa (Kawazoe et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…However, although the antigenic composition of sporozoites has been well documented (Wisher 1986, Sutton et al 1989, Gurnett et al 1990 relatively little is known about the antigens which are present in the first asexual generation or the cross-reactivity of these antigens with those of other asexual generations. The results of experiments in which birds were immunized with the precocious WIS-F-96 line and then challenged with either oocysts or second generation merozoites of the normal parent WIS strain, showed that there is only limited cross-protection between asexual stages and, demonstrated moreover, antigenic differences between sporozoites, first and second generation merozoites (McDonald et a/. 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic diversity among asexual generation merozoites has been noted in the E. tenella strain WIS and its precocious derivative WIS-F-96 (McDonald et al, 1988). WIS-F-96 lacks the second and third generations of schizogony, but yet is highly immunogenic.…”
Section: Coccidia Antigens Associated With Asexual Stages Of Developmentmentioning
confidence: 99%
“…For example, studies on precocious lines of Eimeria (Shirley and Bedrnik, 1997) demonstrated that lines with abbreviated life cycles could still induce protection (McDonald et al, 1986(McDonald et al, , 1988). An inactivated vaccine (NeoGuard) based on tachyzoites of Neospora caninum was developed to prevent Neospora-associated abortion in cattle, and this was recently released in the United States and New Zealand (Reichel and Ellis, 2002).…”
Section: Identifying Vaccine Candidatesmentioning
confidence: 99%